Studies on the growth and mortality of invasive Oreochromis niloticus (Linnaeus, 1758) in sub-tropical river Yamuna, part of Gangetic River system, India. Issue 4 (2nd October 2019) - Alam, Absar; Chadha, Narendra Kumar; Chakraborty, Sushant Kumar; Joshi, Kripal Datt; Kumar, Tarkeshwar; Das, Shyamal Chandra Sukla; Roy, Sibnarayan Dam; Rizvi, Anees Fatima; Sawant, Paromita Banerjee; Kumar, Jeetendra
Abstract : Growth parameters, mortality, growth performance index and exploitation ratio of Oreochromis niloticus were assessed based on the length-frequency data collected fortnightly from the Allahabad stretch of the Yamuna, India, during September 2011 to August 2013. The size of the catch ranged between 70 and 495 mm total length. The data was analyzed using the Electronic Length Frequency Analysis module in FiSAT software. Asymptotic length and growth coefficient were estimated as 562 mm total length and 0.58 year −1, respectively. Total mortality, natural mortality and fishing mortality coefficients were 3.74, 1.015 and 2.725 yr −1, respectively. The growth coefficient index was calculated as 3.26. The exploitation ratio worked out as 0.667, indicated that the stock was slightly overexploited. Estimated growth at the end of I, II and III years was 247, 386 and 463 mm total length, respectively. The observed multi-year survivorship based on the length frequency data from the river Yamuna in O. niloticus suggested that it has successfully established in the non-native environment and is rapidly spreading in other tributaries of the river Ganga. The recruitment pattern was observed to be continuous throughout the year, with several micro-cohorts and two overlapping peaks of unequal pulse strengths. Estimated maximum sustainable yield for this species in the Allahabad stretch of the river Yamuna was 27.13 t. This study can form an important base for future research work in the management of this invasive species in the Gangetic river system in India.